Analisis Wacana Pada Berita "1 Dari 3 Siswa Beresiko Alami Bullying, Nadiem Keluarkan Permendikbud Baru" Di Detik.Com - Siti Nurhamidah; Yogie Alontari (KOMVERSAL, 2024)
This research aims to understand the packaging of the text in the news article "1 in 3 Students at Risk of Experiencing Bullying, Nadiem Issues New Education Regulation" from detikco. Therefore, a problem formulation is necessary. The problem formulation is: How is the Discourse of the Text in the news article "1 in 3 Students at Risk of Experiencing Bullying, Nadiem Issues New Education Regulation" from detikcom? How do the dimensions of social cognition and social context manifest in the news article "1 in 3 Students at Risk of Experiencing Bullying, Nadiem Issues New Education Regulation" from detik.com? The discourse of the text in the news article "1 in 3 Students at Risk of Experiencing Bullying, Nadiem Issues New Education Regulation" can be analyzed through the use of words or language in the text, the sources utilized by the author, as well as the construction in terms of cognition and the social context of the author that also contributesTo the construction of the text. The theory used is the Social Reality Construction Theory. This type of research is an analytical study using a qualitative approach with a social constructivism paradigm. It employs Van Dijk’s analytical framework. Van Dijk not only examines the discourse of the constructed text but also the author’s mindset and analyzes the discourse that develops in society.The research findings indicate that it can be concluded that a text does not emerge from reality as it is, but rather that the reality of the events is constructed by the parties behind the discourse of the text.